Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen (Studi pada Restoran Hotel Yusro Jombang) - Aqidatul Izzah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
Good service quality can guarantee the survival of the company to survive competition in shaping consumer satisfaction. The study aims to determine the effect of service quality (tangible, reliability, responsiveness, assurance, empathy) on customer satisfaction. The population is all consumers of Hotel Yusro Jombang Restaurant while the research sample is 105 respondents. The analysis technique uses multiple linear regression to determine the effect of service quality on customer satisfaction. The results of the study explain that there is a significant partial positive effect between service quality variables consisting of tangible(X1) with tcount value>ttable of 6,173>0,1484, significance of 0,00<0,05, reliability(X2) with tcount value>ttable of 4,328>0,1484, significance of 0,00<0,05, responsiveness(X3) with tcount value>ttable of 2,882>0,1484, significance of 0,00<0,05, assurance(X4) with tcount value>ttable of 4,978>0,1484, significance of 0,00<0,05, empathy(X5) with tcount value>ttable of 5,983>0,1484, significance of 0,00<0,05 on consumer satisfaction(Y) Hotel Restaurant Yusro Jombang. Simultaneously the five service quality variables have a significant positive effect with significance of 0,00<0,05 and the coefficient of determination is 52,1% while the remaining 47,9% is influenced by other variables not discussed in this study. Tangible (X1) variable has a dominant influence on consumer satisfaction (Y) Hotel Yusro Jombang Restaurant.